Associations between sexual health concerns and mental health symptoms among African American and European American women veterans who have experienced interpersonal trauma. (October 2016) - Gobin, Robyn L.; Allard, Carolyn B.
Abstract: African American women are highly represented in the military and have higher rates of interpersonal trauma than European American women, placing them at greater risk for mental health problems and sexual health issues. The current study examined whether African American women would demonstrate differential associations in sexual health and mental health symptoms than European American women. The study included 91 women Veterans (38 African American, 53 European American) who were seeking treatment for posttraumatic distress. African American women demonstrated more severe sexual health concerns compared to European American women. Bivariate associations were observed between PTSD, depression, and sexual health concerns for African American women, whereas PTSD was the only mental health variable associated with sexual health concerns in European American women. A hierarchical linear regression analysis revealed that PTSD and depression in combination contributed significantly to the prediction of sexual concerns in African American women. This study highlights the presence of sexual health concerns in a highly vulnerable population of women, illustrates the impact of PTSD and depression on sexual health concerns, and suggests that race may be an important factor in studying the effect of interpersonal trauma on women's sexual health. Highlights: Examined racial differences in sexual and mental health among women veterans African American women reported clinically significant sexual concerns at higher rates. African American women reported more severe sexual health concerns. PTSD and depression predicted sexual concerns in African American women.